In situ nanoconfinement catalysis for rapid hydrodechlorination of chlorophenol - Raihan, Uddin Sk; Zhang, Jingqi; Chao, Jingbo; Hu, Qing; Coulon, Frederic; Yang, Xiao Jin (Elsevier, 2025)
Chlorinated phenols are highly toxic to human and ecosystem and their biological degradation is difficult. In this work, a novel MgAlNi alloy catalyst was developed for rapid chemical degradation of p-chlorophenol (4-CP) in water under mild conditions via in situ hydrodechlorination (iHDC) without external hydrogen gas supply. A complete conversion of 0.195 mM 4-CP to phenol was achieved within 15 min with a reaction rate constant of 7.65 h−1, 19.4 times higher than that of the traditional Raney Nickel (AlNi alloy) catalyst. The excellent performance of MgAlNi alloy catalyst is attributed to enhanced H2 generation by Mg etching, surface self-reconstruction by growth of in situ layered double hydroxide (iLDH) nanosheets of 0.08–1 nm, exposed active sites of AlNi intermetallic compounds Al3Ni2 and Al3Ni. The findings of this study provide new insights into broader applications of nanoconfinement catalysis to environmental remediation and open a new domain of in situ nanoconfinement catalysis (iNCC).
Keywords: 40 Engineering; 4016 Materials Engineering; 4004 Chemical engineering; Al-Ni intermetallic compounds; Chlorophenol; MgAlNi alloy; In situ hydrodechlorination; In situ nanoconfinement catalysis